Will You Still Need Me When I'm 64, or 84, or 104? The Importance of Speech-Language Pathologists in Promoting the Quality of Life of Aging Adults in the United States into the Future - Bourgeois, Michelle; Brush, Jennifer; Douglas, Natalie; Khayum, Rebecca; Rogalski, Emily (Seminars in Speech and Language, 2016)
In the next two decades, there will be advances in the diagnosis and treatment of the disorders of aging that have the potential to change the way speech-language pathologists (SLPs) are trained and provide services to individuals with a continuum of cognitive communication challenges. SLPs will address the needs of the aging adult who continues to reside in the community and desires to maintain an independent and meaningful life, as well as those who require a supportive residential setting to achieve a satisfying quality of life. Evidence-based strategies and intervention approaches for the range of goals that will address the desired functions of a meaningful life for individuals faced with cognitive communicative challenges are outlined. Institutional barriers to the implementation of documented evidence-based approaches will need to be reduced through a variety of organizational and systems changes. The projected outcome of these changes will be the creation of a person-centered culture of care that promotes dignity, choice, and engagement in meaningful activities through the end of life.
Keywords: Aging adults; dementia; person-centered; quality of life